HUBUNGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH: KAJIAN MENGENAI OTONOMI KHUSUS DI PROVINSI ACEH - yeni Sri Lestari (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
The prolonged conflict in Aceh between the central government and the Free Aceh Movement (GAM) and the earthquake and tsunami disaster in Aceh have added to the long list of dark history of the suffering of the Acehnese people. The peaceful decision agreed upon by the central government with the Aceh government which gave birth to special autonomy in Aceh provided fresh space for improving relations between the two governments. However, the space of freedom that is given is not fully able to control and build good relations easily, because there are still some differences in principles and political views between the central government and the Aceh government so that conflicts still arise. Therefore, this article aims to examine whether the provision of special autonomy will ensure the existence of Aceh remains within the NKRI?, how is the development of the Central Government's cooperation with the Aceh Government?, What are the impacts of special autonomy in Aceh?. This study found that the special autonomy acquired by Aceh sufficiently guaranteed the authority of the Aceh government in regulating its own regional affairs in accordance with the life principles of the Acehnese people, this was inseparable from the ongoing efforts and efforts between the central government and the Aceh government in establishing cooperation for the integrity of the nation . Special autonomy in Aceh provided its own dynamics for the political stability and stability of the Acehnese people. Keywords: Central government, Aceh government, special autonomy